THE PORTRAYAL OF SECTARIAN LEADERS AND THE DEMONS THEY MADE PACTS WITH IN PENGABDI SETAN AND HEREDITARY - Anissa Ayu Adiyana; Nina Fahri Millatina; Nadifa Hasna Nida; Febri Rizki Andriyani; Aranjani Aristiyani; Happy Allam Ma'rufah (LPPM UNISDA, 2026)
The phenomenon of sects in modern horror films depicts the tension between belief, social power, and trauma inherited from patriarchal systems. This research examines the relationship between the sectarian leader and the demon in the films Pengabdi Setan and Hereditary as a representation of power and gender dynamics. A qualitative approach uses Daitz's (1960) theory to analyze the character formation of the sectarian leader. The results show that both films not only depict a pact with the demon but also depict intergenerational inheritance mechanisms that reinforce patriarchal structures and gender inequality. In Pengabdi Setan, the sectarian leader makes a pact with the demon Raminom to obtain offspring and success. In Hereditary, the sectarian leader is not physically visible but controls a family tragedy to summon the demon king Paimon. Both films demonstrate that the sect power does not end after the leader’s death, but rather leaves a legacy of darkness for the next generation. This study contributes to horror studies by highlighting the relationship between power, gender, and collective fear and enriches film studies through an in depth understanding of social anxiety and patriarchal systems in supernatural symbolism.